A quantitative comparison of articles on two pests and two pathogens of biosecurity risk to New Zealand extracted from International and Chinese databases - Xu, B.; Shaw, N.; Gee, M.; Teulon, D.A.J. (New Zealand Plant Protection, 2016)
New Zealands increasing trade and tourism with Asia and especially China brings with it the need to understand the biosecurity risk to New Zealand from these countries This study compared the number of articles on two Chinese horticultural pests and two Chinese horticultural plant pathogens both of biosecurity relevance for New Zealand which were extracted using webbased searches conducted on two international and three Chinese databases There were up to 35 times more articles found in Chinese databases searched with Chinese characters than found in international databases searched with Latin script The quality of information from the articles in any of these databases was not examined Based on these results it would be prudent to explore further the information found in Chinese articles stored in Chinese databases to determine their relevance to New Zealands biosecurity system Searching Chinese databases with Chinese characters in combination with the more usual searches in international databases might ensure a more comprehensive coverage and could help to reduce the biosecurity risk to New Zealand in the future